Alternative splicing and insect ryanodine receptor. Issue 3 (19th June 2019) - De Mandal, Surajit; Shakeel, Muhammad; Prabhakaran, Vasantha Srinivasan; Karthi, Sengodan; Xu, Xiaoxia; Jin, Fengliang
Abstract : Phylogenetic tree of the ryanodine receptor (RyR) family based on maximum likelihood estimation.